A method to map lake ice temperature in urban environments - Paulo Pereira; Luis Valenca Pinto; Miguel Inacio; Damia Barcelo (MethodsX)
Lakes supply a wide range of ecosystem services, including recreation activities. They are very important in urban areas, and in the northern latitudes, recreation activities are relevant in winter when the lake is frozen. To ensure the safety of activities, it is important that the temperature of lake ice be monitored. In this work, we developed a methodological framework to assess ice temperature in lakes during the winter using an Unmanned Aerial Vehicle (UAV). The steps followed were: 1) UAV mission planning, 2) field data collection, 3) mission reconstruction, 4) data extraction, and 5) statistical and spatial analysis. The method developed in this work can be useful for local authorities to assess and monitor ice lake temperature during the winter and ensure the safety of these areas for recreation. The method can be applied to lakes located in different environments. • A new framework was developed to assess and monitor lake temperatures during the winter. • High resolution thermal Unmanned Aerial Vehicle was used to assess lake temperature. • The method can be helpful for local authorities to ensure urban lakes' safety for winter recreation.